First report of Dicrocoelium sp. In hoary fox (Lycalopex vetulus lund 1842) (carnivora: canidae) feces - Barçante, Thales Augusto; Muniz de Paiva Barçante, Joziana; Nascimento Seixas, Josiliene; de Freitas Milagres, Tarcísio; Vogas Peixoto, Juliano; Traversa, Donato; dos Santos Lima , Walter (Revista de Patologia Tropical / Journal of Tropical Pathology, 2024)
The hoary fox (Pseudalopex vetulus), endemic to Brazil’s Cerrado region, is a wild canid species facing ecological pressures from urbanization and habitat fragmentation. These pressures increase the risk of pathogen transmission between wild and domestic animals, particularly in rural and peri-urban areas. This study reports the first instance of Dicrocoelium sp. and Hepatozoon spp. infections in a wild female hoary fox in Southeast Brazil. The fox, presented with neurological disorders, dehydration, and poor nutritional condition, was hospitalized and subjected to a series of parasitological and clinical tests. Blood smears and fecal examinations revealed the presence of Hepatozoon sp. gametocytes and a significant number of Dicrocoelium eggs. The fox received treatment with albendazole, enrofloxacin, and N-acetylcysteine, showing progressive improvement before being reintroduced to its habitat. This study highlights the significance of parasitic infections in wild canids, emphasizing the need for further research on the ecological and health impacts of such infections. It also underscores the importance of comprehensive fecal and hematological examinations in the clinical assessment of wild fauna and raises awareness about the potential of wild canids as reservoirs for zoonotic parasites. KEY WORDS: Zoonosis; one health; canids.